The Effect of on the Job Training Experience and Motivation on Job Readiness of Diploma Three Cadets at the Indonesia Civil Pilot Academy of Banyuwangi - Anggraini, Naulia; Prayitno, Hadi; Setiawan, Rochmad (PT FORMOSA CENDEKIA GLOBAL, 2025)
On the Job Training is a provision of knowledge through motivation that encourages mature work readiness. The purpose of the study is to see how API Banyuwangi three-year diploma programme cadets are prepared, especially motivation and job training. By distributing it to 26 samples of cadets and using SPSS 29 software. The collected data were subjected to validity test, reliability test, multiple regression analysis, hypothesis test, coefficient of determination analysis, and classical assumption test. The study found that On the Job Training is influenced by motivation, both separately and in combination have little effect on work preparation. That is, motivation and On the Job Training amounted to 8.7%, while other variables amounted to 91.3%. This study aims to support academics in improving job training programmes and to obtain more reliable results, it is recommended that future studies involve more people and collect larger sample sizes.